Case Report: Not All Neurological Symptoms Respond Well to Penicillin in Patients With Neurosyphilis - Wang, Xiaoli; Mu, Pengying; Zhang, Wenjuan; Liu, Yonghong (Frontiers in Neurology, 2022)
Patients with neurosyphilis present with a wide range of neurological symptoms, the response of which to penicillin is not well known. In this paper, we analyzed the clinical video-electroencephalogram (EEG) features of neurosyphilis in a 54-year-old man who exhibited with rhythmic orofacial involuntary movements, Argyll Robertson pupil, frequent paroxysmal oral-automatism seizures, periodic lateralized discharges (PLEDs) with triphasic waves, behavioral changes, and memory decline. After treatment with penicillin, PLED and seizures disappeared and behavioral changes and memory decline were significantly improved, but rhythmic orofacial involuntary movements and Argyll Robertson pupil persisted, which indicates an irreversible characteristic of late stage neurosyphilis syndromes.